Dendrobium officinale polysaccharides ameliorated pulmonary function while inhibiting mucin-5AC and stimulating aquaporin-5 expression. (March 2016) - Song, Tian-He; Chen, Xiao-Xin; Tang, Sydney Chi Wai; Ho, James Chung Man; Lao, Li-Xing; Ng, Tzi Bun; Lee, Kai-Fai; Sze, Stephen Cho Wing; Zhang, Kalin Yanbo
Highlights: DOP ameliorated the lung functions and inflammation in COPD patients. DOP down-regulated mucin-5AC expression both in COPD models and patients. DOP up-regulated aquaporin-5 expression both in COPD models and patients. Abstract: Dendrobium officinale has been used in China for several thousand years as a health food and a source of nutrients. In this study, the therapeutic effects of D. officinale polysaccharides (DOP) on chronic obstructive pulmonary disease (COPD) were investigated. Western blot and qPCR techniques were firstly used to determine the effects of DOP on mucin-5AC and aquaporin-5 expression in both in vitro and in vivo COPD models. Thereafter, forty COPD patients were enrolled and randomly assigned to receive placebo or DOP. Spirometry test, ELISA, and immunohistochemistry were employed to measure the lung function, serum and bronchoalveolar lavage fluid pro-inflammatory mediator levels, and mucin-5AC and aquaporin-5 expression in the airway submucosal glands. The results showed DOP could ameliorate the lung functions and inflammation while remarkably decreasing mucin-5AC and increasing aquaporin-5 expression in both COPD models and patients. Our data suggest that DOP could be a promising diet therapy for COPD treatment.